State Bar Voluntary Legal Services Program Conference-Oakland Hyatt - Watkins, Howard::::::::: (1983)
?, Leroy Cordova, Orchid Hubanks (Administrator with Tulare County Legal Services), Randy Lyon (Director of Tulare County Legal Services)